Archaeologies of placemaking : monuments, memories, and engagement in native North America - Rubertone, Patricia E. (One world archaeology, 2008)
The contributors ask critical questions about historic preservation and commemoration methods used by modern societies and their impact on the perception and identity of Native American peoples, who are generally not consulted in the commemoration process.